SIMULASI ANTRIAN KENDARAAN PADA U-TURN DAN DAMPAK TERHADAP KINERJA JALAN PERKOTAAN - Hadid, Muhammad; Widyastuti, hera; Herijanto, Wahju (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
The queue that occurs at U-turn is affecting its performance decreases of urban road performance. The maximum length of queue on Dr.Ir.H.Soekarno Street, Surabaya which is 102 meters decreases its performance. The Simulation is based on Poisson distribution using the arrival rate (λ). The time that used to turn is using formulation of cumulative frequency distribution of the time to turn. The result of the simulation was corrected by correction factor that add it to the turn time. The result of the simulation is length of the queue that is used on the analysis of road performance. The result of analysis is the maximum length of queue is 102 meter with the correction factor is 0.9 second. The capacity of weaving C is decreases from 3960 pcu/h to 3858 pcu/h and the decrease of V/C ration from 0.77 to 0.79 is caused by the length of the queue. In order to reduce the effect of queue is by expand the road width from 8 meter to 11.5 meter. In this condition, the capacity could increase from 3496 pcu/h into 5113 pcu/h and V/C ratio from 0.88 into 0.60.